2016
DOI: 10.3892/or.2016.4813
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid inhibits proliferation and reverses drug resistance of ovarian cancer stem cells by downregulating ABCG2 through suppressing the expression of hypoxia-inducible factor-1α in vitro

Abstract: Hypoxia in tumors is closely related to drug resistance. It has not been verified whether hypoxia-inducible factor-1α (HIF-1α) or ABCG2 is related to hypoxia-induced resistance. Ursolic acid (UA), when used in combination with cisplatin can significantly increase the sensitivity of ovarian cancer stem cells (CSCs) to cisplatin, but the exact mechanism is unknown. The cell growth inhibitory rate of cisplatin under different conditions was evaluated using Cell Counting Kit-8 (CCK-8) in adherence and sphere cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…Next, the effect of tyrphostin RG14620 on ABCG2 protein expression was determined in ABCG2-overexpressing H460-MX20 cancer cells, as it has been shown that drug-induced transient down-regulation of ABCG2 can also lead to the re-sensitization of ABCG2-overexpressing multidrug-resistant cancer cells to chemotherapeutic agents [12, 33, 62]. Cells were treated with increasing concentrations (0 – 2 μM) of tyrphostin RG14620 for 72 h and processed by immunoblotting as described in Materials and methods .…”
Section: Resultsmentioning
confidence: 99%
“…Next, the effect of tyrphostin RG14620 on ABCG2 protein expression was determined in ABCG2-overexpressing H460-MX20 cancer cells, as it has been shown that drug-induced transient down-regulation of ABCG2 can also lead to the re-sensitization of ABCG2-overexpressing multidrug-resistant cancer cells to chemotherapeutic agents [12, 33, 62]. Cells were treated with increasing concentrations (0 – 2 μM) of tyrphostin RG14620 for 72 h and processed by immunoblotting as described in Materials and methods .…”
Section: Resultsmentioning
confidence: 99%
“…This is highly possible, because survivin [ 31 38 ], Mcl-1 [ 39 47 ], XIAP [ 35 , 36 , 38 , 44 , 48 55 ], and cIPA2 [ 55 ] play critical roles in pancreatic cancer resistance to treatment, and it is also known that survivin [ 56 – 69 ], Mcl-1 [ 70 , 71 ] and XIAP [ 54 ] are involved in latent CSC drug resistance and function. Furthermore, it is well documented that ABCG2 as a critical efflux pump protein plays a vital role in maintaining viability of latent stem-like cancer cells [ 23 29 ], and the increase of ABCG2 [ 13 17 ], Pgp [ 18 21 ] expression is important for pancreatic cancer resistance to commonly used pancreatic cancer drugs in the clinic. In this regard, FL118 is not a substrate of these efflux pump proteins [ 12 , 22 ] and can bypass these protein expression-induced treatment resistance [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…FL118 exhibits a favorable pharmacokinetics profile, accumulating and residing in tumors [ 12 ]. Since ABCG2 is a critical efflux pump that maintains viability of latent stem-like cancer cells [ 23 29 ], the capability of FL118 bypassing ABCG2 resistance makes it effective in killing latent, stem-like cancer cell populations and may also overcome the effect of desmoplasia-mediated limitation of drug access to pancreatic tumors. Therefore, development of novel drugs that can overcome ABCG2-mediated treatment resistance is one of the pressing issues in the field of anticancer drug development [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since MDR1 is an HIF-1α target gene and it was reported that UA was capable of inhibiting HIF-1α (Wang et al, 2016), we wondered whether HIF-1α mediates UA-induced MDR1 down-regulation. We observed that under hypoxia, inhibition of HIF-1α resulted in lower MDR1 levels, while MDR1 inhibition did not influence the expression of HIF-1α, confirming the transcriptional regulation of MDR1 by HIF-1α (Figs.…”
Section: Inhibitive Effect Of Ua On Mdr1 Through Hif-1α Inhibitionmentioning
confidence: 99%